Printing ink and overprint varnish formulations : recent developments - Flick, Ernest W. (Noyes Publications, 1991)
This book presents about 300 printing ink and overprint varnish formulations from manufacturers. Types of inks covered include flexors, gravures, heatsets, offsets, quicksets, sheetfeds, lithographics, screen-process, and letterpress inks. Overprint varnish formulations have such major properties as: high solids, high slip, thermosetting, heat resistance, oil resistance, high gloss, scuff resistance. Each formulation may include, in the manufacturer's own words, as available: 1) each raw material contained, 2) percent by weight of each raw material, 3) suggested formula modifications, 4) key properties, and 5) formula source. The book also contains a Trade-Named Raw Materials section and a list of Suppliers' Addresses.
Includes index.
Keywords: Printing ink.; elektronické knihy; electronic books